The Analysis of Drainage Capacity of Balikpapan City - Sari, Liana Mustika; Azmanajaya, Emil; Pongtuluran, Ezra Hartarto (Civil Engineering Dept, Balikpapan State Polytechnics, 2002)
Jalan Sungai Ampal in front of the fresh market of Balikpapan Baru often inundation occurs when it rains. This is due to several factors, one of which is rainwater passing through the drainage channel that exceeds the storage capacity so that the water overflows which causes puddles in the surrounding area. In order for the handling to be carried out effectively, a thorough analysis of the drainage system is needed which will then be used as the basis for determining the handling of inundation. Data analysis in this research uses SWMM 5.1 application. Starting from knowing the cause of inundation to planning the ideal drainage channel capacity. This analysis is also assisted by the google earth application to see thearea subcatchmen, slope and soil elevation at the research site. Simulation of the ideal planned drainage channel capacity is carried out using the trial error method on the SWMM 5.1 application. From this method, the ideal design channel capacity is 1 m. On channel 1 can accommodate 0.574 m3/ sec with a maximum flow of 1.58 m / s and the channel capacity by 60%. On channel 2 can accommodate 0.792 m3/ sec with a maximum flow of 1.15 m / s and the channel capacity by 82%. On channel 3 can accommodate 1.418 m3/ sec with a maximum flow of 2.27 m / s and the channel capacity by 74%. No problem channels were found after re-simulation using the design channel dimensions, so the design diameter of 1 m is considered safe.